Behavior of People Affected by Stunting and Their Prevention in Meler Village and Compang Dalo Village, Ruteng District, Manggarai Regency - Hotlif A. NOPE (Indonesia Strategic Sustainability, 2023)
Stunting is still a major problem in Meler Village and Compang Dalo Village, Ruteng District, Manggarai Regency, so it is necessary to know the behavior of people affected by stunting and their prevention mechanisms. The method used in this study is a qualitative research method, with a case study approach with a total of 37 informants in this study while the types of data in this study are qualitative data and quantitative data and data collection techniques in this study are observation, qualitative interviews and documents. -qualitative documents. The data that has been collected is then analyzed using data analysis techniques from Bungin (2012: 70), namely; (a) Data Collection, (b) Data Reduction, (c) Data Display and (d) Conclusion Drawing and Verification. The results of the study found that the behavior of people affected by stunting in the area of Meler Village and Compang Dalo Village, Ruteng District, Manggarai Regency was by doing; (a) specific nutrition interventions, (b) sensitive nutrition interventions while for stunting prevention behavior in the Meler Village and Compang Dalo Village areas, Ruteng District, Manggarai Regency, is to carry out; (a) fulfilling nutritional needs since pregnancy, (b) giving exclusive breast milk (ASI) until the baby is 6 months old, (c) accompanying exclusive breastfeeding with complementary foods for healthy breast milk (MPASI), (d) continuing to monitor growth and development children and (e) keeping the environment clean.